Authors (The Biblical archaeology review, 2025)
Matthew J. Adams (In the Shadow of Armageddon) is director of the Jezreel Valley Regional Project and former director of the W.F. Albright Institute of Archaeological Research in Jerusalem. Drew W. Billings (Biblical Profile: Paul, the Bible’s Last Action Hero) is Associate Professor in the Department of Philosophy and Religion at the University of Mississippi. […]